Expectations of patients towards general practitioners in Poland - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
Introduction Primary healthcare in Poland plays a key role in the whole public healthcare structure in Poland. Professionals employed in this sector meet not only health needs of patients but also psychological and emotional ones. Primary health care also contributes to the social and economic development of the society. The one of strategic goals of primary healthcare in Poland is to provide satisfaction with its services, which is strictly related to patients expectation towards general practitioners. Objective The purpose of this study is to present how expectations of patients towards general practitioners are depicted in professional literature. Results Analysis of presented studies showed that patients of Polish primary healthcare practices mainly expect discussion about the health problem and comprehensible information on how to deal with their illness. On the other hand one large-group study revealed that patients await on the first place effectiveness of treatment, professionalism of the practitioner and the solution of the their problem. Although, explaining and informing was also very frequently chosen answer in the questionnaires. Polish patients of general healthcare services relatively rarely expect emotional support, but seeking some kind of psychological help may be even the main reason for visits of patients over 65 to a primary care physician. This is crucial issue as many patients who met general practitioners with their complaints are from geriatric age group. Conclusions A satisfactory exploration of the patients’ expectations in primary health care conditions seems to be pivotal for an good communication with patients and providing adequate healthcare. Lack of understanding of the patient’s needs and lack of coping skills with patients who primarily expect to be able to talk to their doctor and receive comprehensive information, explanation of medical problem and emotional support, may be a source of dissatisfaction with the visit of both the doctor and the patient.